2022
DOI: 10.1097/jcp.0000000000001536
|View full text |Cite
|
Sign up to set email alerts
|

Adverse Effects After Ayahuasca Administration in the Clinical Setting

Abstract: and consult an ophthalmologist immediately. Also, according to the literature, drug-associated acute ACG is believed to be idiosyncratic in nature. That is to say that the ocular adverse effects, unlike the systemic ones, are not dose related, 6 as illustrated in this case report-our patient received only 100 mg of topiramate per day, whereas the recommended clinical dose for approved indications is 200 to 400 mg daily. Supporting its idiosyncratic nature, 3 different reasons can be pointed out: (1) a very sma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…The most significant negative experience in the study was a transient dysphoric episode that included agitation, confusion, anxiety, dissociation/derealization, and visual changes (in the placebo-ayahuasca group). The full report on this case and how it was managed can be found in a previous publication under “Case 2.” 49 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The most significant negative experience in the study was a transient dysphoric episode that included agitation, confusion, anxiety, dissociation/derealization, and visual changes (in the placebo-ayahuasca group). The full report on this case and how it was managed can be found in a previous publication under “Case 2.” 49 …”
Section: Resultsmentioning
confidence: 99%
“…Brain-derived neurotrophic factor plasma levels were measured as a biological proxy of increased neuroplasticity. 49 Plasma levels of total BDNF were measured by enzyme-linked immunosorbent assay according to the manufacturer's instructions (catalog number DBNT00; Total BDNF Quantikine ELISA Kit, R&D Systems). We used the same quantification method as in our previous trial with healthy volunteers.…”
Section: Brain-derived Neurotrophic Factormentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding the occurrence of more significant adverse events in clinical trials with ayahuasca performed by our group, there is a detailed report of the two instances where these effects had to be managed by our research team, how the situation was resolved, and an initial nine step guideline on managing this kind of occurrence [ 76 ]. Overall, it seems that as with other psychedelic administration, a cautious and detailed selection of the volunteers who are allowed to participate in the trials and a supportive setting constructed by researchers has been demonstrated to be enough to reduce and manage the occurrence of AEs in clinical trials.…”
Section: Safety and Tolerability Of Ayahuasca Administrationmentioning
confidence: 99%
“…Furthermore, with the current published data it is very challenging to determine the optimal DMT to β-carboline ratio and dosages that maximize the therapeutic effects while also minimizing the occurrence of AEs. This and other challenges associated with standardized ayahuasca medicinal use (and other psychedelics) go beyond the main focus of this article and have been thoroughly discussed elsewhere [ 74 , 75 , 76 , 87 ] .…”
Section: Ayahuasca’s Alkaloid Contentmentioning
confidence: 99%